THE EFFECTIVITY OF FIRST PARTY PROFESSION CERTIFICATION INSTITUTION OF STATE VOCATIONAL HIGH SCHOOL IN JOGJAKARTA - Budi Santosa (Pondok Pesantren Modern Islam Assalaam, 2018)
First Party Professional Certification Institution /FPPCI has the duty to perform competency based assessment/CBA and certify students of Vocational High School/VHS. This study aims to find out how effective FPPCI in Yogyakarta VHS in conducting CBA/certification profession. The result of the calculation shows that: (1) the percentage of graduation level of CBA in Yogyakarta is moderate, (2) there is a positive and significant correlation between learning achievement with thepassing level of CBA, (3) no relation between work attitude and graduation level of CBA, (4) there is a positive and significant correlation between learning achievement and learning attitude with graduation level of CBA, (5) there is a mathematical model to predict graduation level of CBA.